Herramientas y mecanismos jurídicos para una recaudación tributaria eficiente destinada a viabilizar la función social de la tributación - Fiallos Chiriboga, Jorge Isaac (2015)
In the contemporary age, the main consideration required by the state for social life corresponds to taxes. For this purpose, they have issued rules governing tax management and have led to the delimitation of tax law. The Tax Administration is coated with the determiner faculty, decisive power, regulatory power, collecting power and impose sanctions. Through these powers, the Tax Administration collects taxes that are intended for the benefit of the community and the execution of works of national interest. To improve the efficiency of Revenue is necessary to enhance the collecting power of the tax authorities, thus, it will ensure that the collection is conducted in an effective, transparent and voluntarily. The efficiency of tax collection is not reflected in the amount collected but voluntary act of the taxpayer meets the tax liability. To strengthen tax collection is necessary to implement certain mechanisms and tools to strengthen the collecting power of the tax administration. These include improving computing platforms in order to implement a system of online inquiries and complaints, creating the Taxpayer Ombudsman and the strengthening of the Administration Office in order to avoid litigation.